Examining the Impact of Learning Motivation and Campus Environment on Students’ Performance in Arabic Reading (Muthala’ah): A Study at UIN Datokarama Palu - Sinoso, Fazriaturrahma; Harun, Ubay; Hilmar, Muamar Ahsanul (Albariq: Jurnal Pendidikan Bahasa Arab, 2025)
Abstract This research examines the influence of learning motivation and the campus environment on the learning outcomes of muthala'ah courses for PBA UIN Datokarama Palu students. The method used is a quantitative approach with correlational design and multiple regression analysis. The study population consisted of 54 students in the 6th semester, with saturated sampling techniques. The research results showed that learning motivation had a significant effect on learning outcomes, with a significance value of 0.006 < 0.05 and a value of 2.892 > 2.007 ( ), and the campus environment also had a significant effect, with a significance value of 0.037 < 0.05 and a value of 2.147 > 2.007 ( ). Simultaneously, the two variables had a significant effect with a significance value of 0.000 < 0.05 and an value of 14.192 > 3.18 ( ). The coefficient of determination (R²) obtained was 0.358, which shows that 35.8% of variations in learning outcomes can be explained by learning motivation and campus environment, while 64.2% were influenced by other variables that were not studied.